Direct spectrofluorimetric methods as alternatives to compendial ones used for the quality control of biopharmaceuticals: development, validation and application - Thallis Martins Souza; Robert da Silva Angelino; Larissa Manhães Ornella; Eduardo dos Santos Ribeiro; Simone Ferreira Rodrigues Fernandes (Universidade de São Paulo, 2024)
Abstract A simple, rapid, precise, accurate and sustainable spectrofluorimetric method (SFM) was developed, validated and applied for the determination of 4-aminobenzoic acid and aromatic amino acids (phenylalanine, tryptophan and tyrosine). These compounds are used in biopharmaceutical formulations and therefore must be analyzed by quality control laboratories to meet the criteria established in pharmacopoeias. In general, potentiometric titration (PT) is described in the compendia as the official analytical technique. However, this method showed low sensitivity and selectivity, and moreover was performed with a non-aqueous solvent (acetic acid), which led to higher consumption of reagents and consequently to the formation of residues. Therefore, the SFM was developed in aqueous medium at pH 7.2 using phosphate buffer. It was successfully validated according to the ICH guidelines and showed good linearity range (r>0.999), specificity, accuracy and precision (within and between days) and robustness. The test results were compared between the SFM and PT using raw material samples, while according to the F- and t-tests at 95% confidence level, no statistical difference was found between the methods.